2021
DOI: 10.2981/wlb.00774
|View full text |Cite
|
Sign up to set email alerts
|

Shrub density effects on the community structure and composition of a desert animal community

Abstract: Positive interactions between shrubs and animals are frequent in desert ecosystems. Shrub canopies can provide refuge to some animal species from predators and shelter from stressful environmental conditions by ameliorating high temperatures through lowering the amplitude of variation. Consequently, there have been many contrasts of shrub versus open effects; however, we extend this approach further by testing these effects on a gradient of shrub densities in the Carrizo National Monument, California. We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 75 publications
2
38
0
Order By: Relevance
“…With more shrubs, there are likely more opportunities for positive associations as even relatively small shrub individuals provide benefits (Gaudenti et al, 2021;Lortie et al, 2018;Zuliani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With more shrubs, there are likely more opportunities for positive associations as even relatively small shrub individuals provide benefits (Gaudenti et al, 2021;Lortie et al, 2018;Zuliani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To build off that work and to further examine the relationship between shrub density and lizard presence (Germano et al, 2011), we examined here whether shrub density could also be used, in addition to cover, to predict G. sila presence. Shrub density was selected for this study to further build on the finding previously reported by Zuliani et al (2021Zuliani et al ( , 2023 that shrub density influences the abundance and richness of local desert species while acting as an indicator of overall animal abundance. Here, we hope to extend these findings to a federally endangered species and show that shrub density is easier-and thus potentially cheaper and more cost effective for rapid rangewide surveys-to measure, both in the field and with satellite-based data.…”
mentioning
confidence: 99%
“…At the end of the active season, we collected data on D. ingens burrow densities at each site by counting the number of active or recently inactive burrows (Bean et al., 2012) within 10 m along four 100‐m randomly placed transects at each site. We compared the burrow densities at the Shrubbed and Shrubless sites with Welch's t ‐test in R. We also collected data on perennial shrub densities by counting the number of perennial shrubs in a 10‐m radius around 16 random points (Zuliani et al., 2021) at each site, and compared the densities with Welch's t ‐test in R.…”
Section: Methodsmentioning
confidence: 99%
“…Interacting individuals can experience both negative and positive associations with other organisms. These positive associations are typically the main focus of many plant–plant studies (Stachowicz 2001, Kikvidze and Callaway 2009, Van der Merwe et al 2021); however, positive plant–animal associations are more recently being examined (Vázquez et al 2015, Westphal et al 2018, Zuliani et al 2021b). Facilitation is a non‐trophic interaction between species where at least one individual benefits, while the other either benefits or is unaffected (Molina‐Montenegro et al 2016).…”
Section: Introductionmentioning
confidence: 99%